Low-intensity pulsed ultrasound affects proliferation and migration of human hepatocellular carcinoma cells - Mingzhen Yang; Zhihui Lu; Bangzhong Liu; Guanghua Liu; Mingfang Shi; Ping Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Low-intensity pulsed ultrasound (LIPUS) is an effective ancillary treatment modality for various malignancies. However, the mechanisms underlying the role of LIPUS in cancer treatment have not been fully elucidated. We investigated the effects and underlying mechanism of LIPUS on the proliferation, apoptosis, migration, and invasion of hepatocellular carcinoma (HCC) cells. Methods The HCC cell lines SMMC7721 and HCCLM3 were exposed to 1 MHz LIPUS at intensities of 0.5, 1.0, 1.5 W/cm2 for 60 s. Cell morphology, viability, apoptosis, colony formation, migration, and invasion were assessed. Intracellular reactive oxygen species (ROS) levels and mitochondrial membrane potential were evaluated using a ROS assay kit and a JC-1 staining kit. Western blotting was performed to quantify changes in matrix metallopeptidases and epithelial-mesenchymal transition-related proteins. Orthotopic Hep3B-Luc tumor-bearing mice were treated with LIPUS at 1.5 W/cm2 or 0 W/cm2 and growth trend was measured. Results The results showed that different intensities of ultrasound affected cellular activity, inhibited cell proliferation and cloning, facilitated intracellular cytoskeletal protein reorganization, and induced cell apoptosis, particularly at the intensity of 1.5 W/cm2, through the ROS/mitochondria pathway. LIPUS enhanced SMCC7721 and HCCLM3 cell migration and invasion in a dose-dependent manner by regulating matrix metallopeptidases and epithelial-mesenchymal transition-related proteins. In vivo experiments confirmed the inhibitory effect of LIPUS at 1.5 W/cm2 on tumor growth. Conclusions Although LIPUS induced cell apoptosis and inhibited cell proliferation, it also promoted the invasion and metastasis of HCC cells under certain conditions, which was related to the regulation of matrix metallopeptidases and epithelial-mesenchymal transition-related proteins.